2011
DOI: 10.1007/s11270-011-0927-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Microbial Community Function and Structure in Rehabilitated Asbestos and Coal Discard Sites

Abstract: Previous studies have made some progress with the use of microbial community properties as assessment criteria for rehabilitation success of postmining areas. Currently, there is a need for reference ranges of specific properties in rehabilitated postmining sites to make this approach more practical. The aim of this investigation was to compare assessment parameters indicative of microbial community function (enzymatic assays) and structure (phospholipid fatty acid (PLFA) analysis) in rehabilitated asbestos an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…However, the proportions of GNB tend to increase when stress situations have ceased (Bardgett et al 2001;Romaniuk et al 2011). Other studies also have shown that soil moisture regimes can have great influence on the whole microbial communities (Bardgett et al 1999;Claassens et al 2012;Swallow et al 2009). …”
Section: Seasonal Effect On Soil Microbial Community Structurementioning
confidence: 96%
See 4 more Smart Citations
“…However, the proportions of GNB tend to increase when stress situations have ceased (Bardgett et al 2001;Romaniuk et al 2011). Other studies also have shown that soil moisture regimes can have great influence on the whole microbial communities (Bardgett et al 1999;Claassens et al 2012;Swallow et al 2009). …”
Section: Seasonal Effect On Soil Microbial Community Structurementioning
confidence: 96%
“…In mined areas, 19:0cy/18:1x7 ratio significantly decreased with time after re-vegetation and with the improvement of soil nutrients (Zhang et al 2012). According to Claassens et al (2012), the increase of 19:0cy/18:1x7 ratio indicates higher levels of stress in coal and asbestos discard areas.…”
Section: Effect Of Re-vegetation On Soil Microbial Community Structurementioning
confidence: 99%
See 3 more Smart Citations